Híbridos crípticos oriundos de populações submetidas à seleção recorrente recíproca de milho - Pospiesz, Diego Avila (2021)
Corn is of great importance in the world agricultural scenario, being the most cultivated grain in the world. The advancement of agriculture and the growing demand for food in the world meant that several techniques involving the genetic improvement of corn were developed, among them is that of cryptic hybrids, which has great potential for the synthesis of superior strains. In this method, two populations are conducted, aiming to obtain complementary strains between them. Because it is poorly studied, information about it in the literature is scarce. The objective of this work was to select among the evaluated hybrids, the two most productive hybrids, mainly for the character of spiked ears and severity to white spot, and based on the selection of these hybrids, select the pairs of progênies that gave rise to them to continue to the cryptic hybrid program at the Federal University of Lavras. The experiment was evaluated in the municipalities of Lavras, Lambari and Ribeirão Vermelho, in the 2018/2019 and 2019/2020 harvests. Six cryptic hybrids from the crossing of ten progênies were evaluated, which in turn were taken from two S1 populations of UFLA's recurrent maize selection program, along with the witnesses the commercial hybrids: 2B810 and DKB177. The experiment was conducted using a randomized block design. The plots were constituted each by 2 lines of 4.0 meters spaced in 0.6 m and with four repetitions. The following characters were evaluated: Grain productivity, weight of spiked ears, number of grains per ear and severity of white spot. The data were analyzed with the aid of the Genes software. Analyzes were made separately for the harvest and off-season, for all characters except. The analysis of joint variance was significant at 5% confidence for the characters weight of unshelled ears, weight of 100 grains, number of grains per row and severity by white spot, there was a significant difference of at least 5% for both hybrids, for off-season progênies, and for harvest. it was possible to select the best hybrids for both the off-season and the crop, being among the three most productive hybrids, both in the crop and in the off-season, the A3xB3 and A4xB4 hybrids, and also presented the lowest severity of the white spot hybrids. In view of these results, it is recommended to continue the breeding program, using progênies A4, B4, A3 and B3.